Implementation of Government Policy Through Complete Systematic Land Registration in the Context of Accelerating Certificate Services in Indonesia - Suwari Raturandang; Tjempaka (Journal of Law, Politic and Humanities, 2025)
The increasing population and need for land in Indonesia has made legal certainty over land very important. Many people own land but do not have official certificates, which leads to legal uncertainty and potential land disputes. The purpose of this study is to analyze the implementation of the PTSL policy, the challenges faced, and the expected impact of accelerating land certificate services in Indonesia. This research uses a normative method with a statutory approach, relying on secondary data from various official sources such as government documents, books, research reports, and legal literature. The results show that PTSL is more effective than the previous policy, the National Agrarian Operations Project (PRONA), which was limited by budget and area coverage. PTSL has a more comprehensive approach by targeting all land parcels in one village, thus providing land certificates to more people. The program has improved legal certainty, reduced land disputes, and supported economic development by providing greater access to credit and investment. This demonstrates that government policy through PTSL can be an effective model for better, inclusive, transparent and equitable land governance, and contribute to improved community welfare and national economic development.